Wuliangye Group : digitalization in marketing - Li, Donghong; Li, Xiaohui; Zhou, Pinglu (London : Tsinghua University School of Economics and Management, 2019)
Traditional manufacturers in the digital era are under pressure to create customer value in an environment of rapidly changing customer buying patterns, and their existing connections with customers no longer give them sustainable competitive advantages. Therefore, the ability to deliver value to customers and get customers engaged in the creation of business value has become a crucial objective in achieving sustainable business growth.As a leading enterprise in liquor production, Wuliangye Group holds an important position in the traditional liquor market. In this case, digital transformation started in the company's marketing function because it is the closest to the market, and can benefit from data asset acquisition as well as value creation and acquisition. Firstly, this case details the Group's practical journey on the path to digital marketing. This path includes organizational changes, profit distribution, customer participation, distribution channels, data resources and much other content. Secondly, the case highlights the Group's acquisition of substantial data assets and its formation of digital capabilities, starting with marketing, along with the actions that have laid a foundation for digital transformation of other business areas. This progressive strategic renewal may mitigate the resistance to digital transformation. In the course of driving deeper digital reform, further discussion and analyis should focus on whether Wuliangye Group can realize effective use of data resources and digital transformation of the enterprise as a whole based on data acquired from marketing.
Originally Published InLi, D., Li, X., & Zhou, P. (2019). Wuliangye Group: Digitalization in Marketing. 0-920-362. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wuliangye Group -- Case studies; Internet marketing -- Case studies; Corporations -- Growth -- Case studies